IMPLEMENTASI DAN DAMPAK E LITIGASI DALAM PERSPEKTIF HUKUM ACARA PERDATA DIHUBUNGKAN DENGAN PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2019 - Yeni Nuraeni; Firman Pratama (Universitas Majalengka, 2022)
The development of the era in the Revolution 4.0 era where there was a leap of progress towards digital, the world of justice was also required to follow the developments of the era, coupled with the occurrence of the COVID-19 pandemic which required people to avoid direct interaction. Electronic Judiciary or E-Litigation is a solution for all which is a form of implementation of the legal principle of costante justitie (quick trial and low cost) and it is hoped that this E-Litigation can penetrate the barrier to the effectiveness of the judiciary and is expected to overcome geographical constraints and reduce the high cost of litigation. and become a solution during a pandemic. This study aims to find out how the implementation of E-Litigation in the Majalengka District Court is based on supporting theories and Supreme Court Regulation (PERMA) 1 of 2019, and the Civil Procedure Code, and what impacts occur after the implementation of E-Litigation. The method used in this study is descriptive analysis by analyzing existing regulations regarding E-Litigation and their application in the field, with a normative juridical approach, which basically uses the rules in the applicable legal provisions such as the articles in the legislation. invitation and expert opinion (doctrine), The results of this study indicate that most of the implementation of E-Litigation in the Majalengka District Court is in accordance with the existing PERMA, but if you look at the Civil Procedure Code there are many differences and contradictions in it which are one of the obstacles and also the lack of public knowledge about the procedures. trial with this E-Litigation system. However, the Majalengka District Court continues to actively carry out socialization not only to the general public but also to other legal practitioners.